Penerimaan Konsep Green Hospital di Rumah Sakit Pemerintah (Studi Kasus RSUD Tugurejo Provinsi Jawa Tengah) - Damayanti, Wida Ayulia; Raharjo, Mursid; Agushybana, Farid (HIGEIA (Journal of Public Health Research and Development), 2021)
tributors of climate change and global warming. The success of green hospital implementation depends on the leader’s commitment and acceptance from all employees. This study aimed to analyze the level of acceptance from the hospital’s employees on the concept of green hospital at Tugurejo General District Hospital, Central Java province. This study used a pre-experimental design with one group pretest – posttest. This study was conducted in March to April 2020. There were 300 employees as the samples selected by using a random sampling technique. The data analysis was done in Smart PLS 3.0. The results showed the variables of innovation characteristics, knowledge, and leader’s role significantly gave a positive effecton the employees’ acceptance of the concept adoption. However, communication channel did not affect their acceptance of the concept. The Smith-Satterthwait test showed innovation characteristics, knowledge, and leaders’ role towards the employees’ commitment in the pretest were significantly different from the posttest. Keywords: Green hospital, adoption, innovation, hospital